Design and performance boost of a MOF-functionalized-wood solar evaporator through tuning the hydrogen-bonding interactions - Lu, Yi; Fan, Deqi; Shen, Ziyi; Zhang, Hao; Xu, Haolan; Yang, Xiaofei (Nano energy, 2022)
Interfacial solar evaporation technology is recognized as one of the most promising strategies to address freshwater scarcity issues. To realize the sustainability of this technology for producing potable water from seawater and contaminated water sources, multi-functional photothermal materials need to be explored to attain higher vapor output at the same solar energy input. Herein, a novel wood-based solar evaporator composed of porous wood substrate, zeolitic imidazolate framework-8 (ZIF-8), and polydopamine (PDA) as a light absorption layer is developed. The in-situ loading of ZIF-8 in the microchannels renders the wood evaporator an important function of reducing the equivalent evaporation enthalpy due to the lowered hydrogen bonding density of water molecules when they pass the wood channels, substantially augmenting solar evaporation efficiency. A superior evaporation rate of 2.70 kg m−2 h−1 is achieved under 1.0 sun irradiation, which exceeds the theoretical limit of a typical 2D photothermal evaporator (~1.46 kg m−2 h−1). The designed wood/ZIF-8@PDA also exhibits a prominent removal efficiency for harmful ions and organic pollutants. This multifunctional wood-based solar evaporator shows great potential for future freshwater production. [Display omitted] A MOF functionalized wood-based photothermal evaporator is designed for cost-effective and highly efficient solar steam generation. The MOF grown in wood channel is able to significantly lower the evaporation enthalpy, thus realizing an extremely high evaporation rate of 2.7 kg m−2 h−1 under 1.0 sun irradiation. •A MOF functionalized wood-based photothermal evaporator is fabricated for highly efficient solar steam generation.•In-situ synthesized MOF in wood channel can lower the hydrogen bonding density, thus lowering the evaporation enthalpy.•An extremely high evaporation rate of 2.7 kg m−2 h−1 is achieved under 1.0 sun.•Scalable and highly efficient photothermal evaporators for practical applications